Ulovlig påvirkningsvirksomhet i samarbeid med fremmed etterretningstjeneste - Martin Hennig (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract In 2019, the Danish Parliament amended its Criminal Code, and introduced a ban on the participation in »unlawful influence activities conducted in cooperation with foreign intelligence services«. The ban is far-reaching, and is intended to criminalize participation in influence activities that can affect decision-making or the general public opinion in Denmark. According to Danish authorities, Denmark is facing a sustained threat to national security from hostile states, and the wide-reaching ban on »unlawful influence activities« is deemed necessary to counter such offences aimed at the Danish authorities and the general public. In 2021, Norwegian legislators have proposed a similar ban, which is, to a large extent, based on the Danish criminal provision. This article argues that the ban on »unlawful influence activities « contains vague and imprecise terms, which are contrary to the qualitative requirements of Article 7 of the European Convention on Human Rights, notably those of accessibility and foreseeability. Given the vague wording of the Danish and the proposed Norwegian provisions, it will be very challenging for citizens to regulate their conduct in accordance with the law. The author contends that cooperation with foreign intelligence services should be punishable by law, but that the vague wording of the Danish and the proposed Norwegian ban may limit public debate and cross-border interactions in the area of media and communications. Furthermore, it is argued that national security agencies should aid citizens in identifying what constitutes »unlawful influence activities«, and provide further criteria which can enable citizens to recognize »foreign intelligence services« with whom cooperation is prohibited.